2020
DOI: 10.1186/s40537-020-00367-w
|View full text |Cite
|
Sign up to set email alerts
|

A predictive noise correction methodology for manufacturing process datasets

Abstract: In manufacturing processes, datasets intended for data driven decisions are majorly generated from time-sequenced sensor readings. Industrial sensor systems are prone to transmit inaccurate readings, which result in noisy datasets. Noisy datasets inhibit machine learning and knowledge discovery. Using a multi-stage, multi-output process dataset as an experimental case, this article reports a methodology for replacing erroneous sensor values with their predicted likely values. In the methodology, invalid values… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…However, selecting, processing, monitoring, and applying DA models on real-time data is still a challenging issue in SCM. It can be beneficial for future studies to provide realtime analysis with applying streaming data in their DA models in smart SC, especially for routing and allocation as well as for sustainability problems (Oleghe, 2020). This research gap is also identified in current literature, which also emphasizes the need for real-time, cloud-based data sharing and storage as well as respective DA models to enable realtime DA in SCM (Udokwu et al, 2022).…”
Section: Enabling Real-time Da In Scmmentioning
confidence: 99%
“…However, selecting, processing, monitoring, and applying DA models on real-time data is still a challenging issue in SCM. It can be beneficial for future studies to provide realtime analysis with applying streaming data in their DA models in smart SC, especially for routing and allocation as well as for sustainability problems (Oleghe, 2020). This research gap is also identified in current literature, which also emphasizes the need for real-time, cloud-based data sharing and storage as well as respective DA models to enable realtime DA in SCM (Udokwu et al, 2022).…”
Section: Enabling Real-time Da In Scmmentioning
confidence: 99%
“…This results in BD inequality [32]. Unfortunately, studies dealing with BD integration with an HCPS, e.g., [33][34][35][36], have not yet addressed BD inequality. For example, consider the work in [33].…”
Section: Preparing Datasets Of Surface Roughness For Bdmentioning
confidence: 99%
“…The creation of the paper to stop the electrical discharge process with projected output value depends on this paper. Oleghe [10] developed a methodology to deal with missing and invalid value correction in process datasets. This is a big data-induced problem in Manufacturing.…”
Section: Introductionmentioning
confidence: 99%